Unilateral intestinal lung disease misdiagnosed as rheumatoid lung disease. A case report of absent pulmonary artery - Bimaje Akpa; Hem Desai (Respiratory Medicine Case Reports, 2024)
Unilateral absence of pulmonary artery (UAPA) is a congenital clinical abnormality that is rarely diagnosed in adulthood. Due to its rarity and heterogeneity as it pertains to its clinical presentation, it may be difficult to diagnose, often leading to misdiagnosis. We present a case of UAPA with unilateral pulmonary fibrosis which was misdiagnosed as rheumatoid arthritis-associated interstitial lung disease (RA-ILD). We describe the symptomology, physical examination findings, laboratory values and radiologic findings. We also describe the diagnostic challenges and approach to a patient presenting with unilateral interstitial lung disease (ILD) and highlight the importance of a comprehensive evaluation.